Correction and compensation of I/Q imbalance and multipath channel - Haq, Khandker Nadya (Curtin University, 2015)
This thesis presents adaptive schemes in overcoming signal distortion, caused by l/Q imbalance and multipath propagation, for OFDM and single carrier modulation. A combined correction and compensation scheme has been presented to mitigate the l/Q imbalance and channel for OFDM. The proposed scheme has been compared with three existing schemes. Simulations show that it successfully outperforms the other existing schemes. Similarly, for single carrier modulation two schemes have been presented for l/Q and channel mitigation.